Men behaving appropriately: integrating the role passing technique into the ALOHA system - MACNAMEE, BRIAN; DOBBYN, SIMON; CUNNINGHAM, PADRAIG; O'SULLIVAN, CAROL ANN (My University, 2002)
The Adaptive Level of Detail for Human Animation (ALOHA) system is a platform for animating virtual humans within a virtual environment using levels-of-detail for geometry, motion and conversational behaviour. Until now the behaviour of these humans has been determined using pre-defined scripts. This paper describes the integration of the intelligent agent based role-passing technique into the ALOHA system to allow for the creation of dynamic scenes.
PUBLISHED
Keywords: virtual environments; human animation